Perencanaan Sistem Distribusi Dengan Analisa Aliran Daya - Hari Prasetijo (Dinamika Rekayasa, 2007)
This paper presents system distribution planning study with minimum investment base for 10 years. The planning will begin from existing condition (first year) and shows migration of system growth from first year  until tenth year. The planning constrain are voltage criteria and equipment capability. The study use  distribution power flow analysis as metode. The result of this study is distribution power flow analysis can  predict equipment profile that out of criteria and this condition make the planning more efective.